Mechanism and implications of pro-nature physical activity in antagonizing psychological stress: the key role of microbial-gut-brain axis - Lou, Hu; Liu, Xue; Liu, Ping (Frontiers in Psychology, 2023)
Appropriate physical activities and a biodiversity-rich environment are conducive to the relief of psychological stress, and pro-nature physical activities are a combination of the two, which has good application potential in antagonizing psychological stress, but the intervention mechanism is still unclear. The microbiota-gut-brain axis is cyclically associated with psychological stress, and psychological stress can affect the microbiota through the gut-brain pathway, and conversely, the microbiota can also affect the psychological stress-induced symptoms. It is suggested that the microbe-gut-brain axis may provide a new perspective and target for the treatment of psychological stress-related diseases. Pro-nature physical activity can improve the number of Firmicutes, short-chain fatty acids, Akkermansia bacteria, and the gut-brain barrier and further affect the HPA axis, BDNF, and serotonin pathways of gut-brain two-way communication, thereby maintaining the body's homeostasis and reducing antagonistic psychological stress. According to the comprehensive influence of physical activities on the microbiota-gut-brain axis, a "green + exercise prescription hypothesis" in line with the holistic medical concept is revealed, which is expected to be effective in the prevention, alleviation, and treatment of irritable bowel syndrome and neurodegenerative diseases. It provides new means for treating psychological stress-related diseases such as mental disorders and mood disorders. In addition, it enlightens the construction of green infrastructure that is conducive to the diversified contact of microorganisms in outdoor physical activities venues and induces healthy interaction between the human body and the microbial population in the natural ecology. However, the current research is still in its early stages, and the intervention effect and mechanism of pro-nature physical activities need further demonstration in the future.